Innovative Rheumatology - Matsuno, Hiroaki (IntechOpen, 2013)
In recent years, the treatment of Rheumatoid Arthritis has undergone tremendous changes due to methotrexate and biologics in large part. Until a decade ago, avoiding joint destruction in rheumatoid arthritis was not realistic for rheumatologist. However, prevention of joint deterioration is now possible, and the quality of life of patients with rheumatoid arthritis in long-term has been able to improve by advances in treatment. However, there are still many problems to be overcome before achieving the treatment of rheumatoid arthritis. All of review articles presented on this book are explaining treatment, basic research, and patient care of rheumatoid arthritis with innovative perspective and ideas. I hope that the ideas that have been described in these articles help the reader to resolve the outstanding issues in rheumatoid arthritis.